Learning from indigenous youth to build relations and earn trust in policing - Desmoulins, Leisa (Journal of ethnicity in criminal justice, 2022)
As part of a local police service’s larger organizational change initiative, this study explored trust in policing. A cultural safety lens was used to hear Indigenous youths’ truths and experiences. Methods comprised three focus groups with 19 participants (age 18-30 years) in the spring of 2019. Researchers employed a three-phase procedure to code and analyze the data. Findings highlight factors that led to participants’ mistrust and perceptions of biased policing. Participants also recommended four ways for police to gain their trust through education, community engagement, respectful relations, and accountability. Implications for practice ensure a culturally safe approach for police and other mainstream organizations to follow for institutional changes that promote trust and reconciliation. Conclusions and next steps follow for an iterative, dialogical process for cultural safety.